A systematic review and meta-analysis of sex differences in cannabis use disorder amongst people with comorbid mental illness. (3rd September 2021) - Kozak, Karolina; H. Smith, Philip; Lowe, Darby J.E; Weinberger, Andrea H.; Cooper, Ziva D; Rabin, Rachel A.; George, Tony P.
ABSTRACT: Background: While males are more likely diagnosed with cannabis use disorder (CUD), females are more susceptible to developing and maintaining CUD. Yet, for both sexes, CUD is associated with high rates of comorbid mental illness (MI). Objectives: To identify and compare sex differences in the prevalence of comorbid CUD amongst individuals with/without MIs. Methods: This systematic review generated pooled odds ratios (OR) and 95% confidence intervals (CI) from 37 studies (including clinical trials, cohort, and case–control studies) among individuals with and without MIs, quantifying sex differences in rates of comorbid CUD. A meta-analysis was also completed. Results: In the CUD-only group, males were twice as likely to have CUD than females (OR = 2.0, CI = 1.9–2.1). Among MIs, males were more likely than females to have CUD comorbid with schizophrenia (OR ~2.6, CI = 2.5–2.7) and other psychotic, mood, and substance use disorders (1> OR <2.2, CI = 0.7–2.6). The reverse association (females > males) was observed for anxiety disorders and antisocial personality disorder (OR = 0.8, CI = 0.7–1.0). Among females, MIs increased the likelihood of having CUD, except for psychotic disorders and depression. A meta-analysis was inconclusive due to high heterogeneity across studies. Thus, comparisons across MI groups were not possible. Conclusion: While males are more likely to be diagnosed with CUD, there are important sex differences in the prevalence of CUD across MI diagnoses that should be taken into account when approaching CUD prevention and determining treatment efficacy.